Alih Teknologi Olahan Oyek di Desa Lumbir Kecamatan Lumbir Kabupaten Banyumas - Abdul Mukhlis Ritonga; Andi Ali Said Akbar; Muhamad Riza Chamadi (Warta LPM, 2022)
Oyek is a healthy alternative food and is needed by various levels of society because it is high in carbohydrates and low in sugar. The production of motorcycle taxis in Lumbir Village still uses traditional methods and processing. In order to be able to penetrate a wider market and be able to increase the economic value of residents, it is important to apply appropriate technology for processing motorcycles. The application of appropriate technology will be efficient and sustainable with the institutional support of solid and skilled farmer groups. Empowerment of farmer organizations through production management and marketing is a necessity. The framework of this service activity was carried out and was welcomed by the residents of Lumbir Village. The activity was carried out using a participatory method by involving the target audience, namely the Mekar Sari farmer group with 24 members, the Sido Rukun farmer group with 20 members and community members to play an active role in the activity and was accompanied by a technology application team who acted as extension workers and facilitators. as well as continuous evaluation and monitoring. The monitoring results are expected to increase the desire and motivation to improve the standard of living and welfare of the target community. This technology transfer has answered the partner’s problems, namely First, the technological aspect: the availability of appropriate technology for processing motorcycles that are more modern, efficient, healthy and of good quality. The technology includes grinding machines, rice granules, solar and gas drying houses and product packaging equipment. Second, the Social Aspect: the service provider has made a social approach to the village government, community leaders and farmers about the benefits of motorcycle production technology. The conclusion is that in general, the application of this technology can increase the economic level of the members of the cassava farmer group, build a more efficient and quality processing system, and increase the economic value of the motorcycle product with the existence of quality motorcycle products, modern packaging and production permits from the government.